NUMERICAL SIMULATION STUDY OF LIGHTWEIGHT-DEFORMABLE PROJECTILE IMPACT 6061-T651 ALUMINUM ALLOY PLATE (MT) - HU Jing; HU Ang; DENG YunFei (Jixie qiangdu)
In order to investigate the ballistic performance, failure patterns and energy dissipation of aluminum alloy target plates against the impact of different strength and head shape projectiles, the three-dimensional models of 3 mm thick 6061-T651 aluminum alloy target plates impacted by lightweight-deformable projectiles of different materials were established by Abaqus finite element software, and the modified Johnson-Cook（MJC） constitutive model and the Lode-dependent modified Mhor-Coulomb（MMC） fracture criterion are used for numerical simulation. The results show that the corresponding ballistic limit velocity of the target plates are the highest when the low strength 6061-T651 aluminum alloy are used as the projectile material, and the ballistic limit velocity of the target plates decrease with the increase of the projectiles strength. The impact will cause a more complex failure patterns of the target plates when the projectiles strength is low, and at the same time, the plastic deformation of the projectiles head occur to different degree; the projectiles strength has a significant effect on the energy dissipation ability of the target plates. The ballistic limit velocity corresponding to the lightweight-deformable blunt-head projectiles are higher than that of the ogival-head projectiles.